Development of employability skill profile for construction skilled workers in Malaysia - Ahmad Zaki, Shazwani (2013)
It is essential that the vocational skill providers understand the skill gap and the requirements of the construction organisations to be able to produce suitable skilled workers. The focus of this study is to identify the skills requirement for the construction skilled workers to work efficiently and be equipped with the necessary attributes to be employed in the construction sector. Essential skills necessary for construction skill workers were identified from the perspectives of the training providers and the construction organisation in Malaysia. This thesis presents the findings of the questionnaire survey among the industry experts, semi structured interviews with the training providers and the validation exercise involving practitioners in Kuala Lumpur and Selangor. The study identified seven important key skills which include Positive Attitude and Behaviours; ability to Work with Others; Responsible; Job Competencies; Communication Skills; Adaptability and Qualification Factors. The skills were ranked according to the Relative Important Index (RII) value. These seven key skills were broken down into 48 elements of skills. However, the analysis shows that, these skills were only applied in the range of 18.4% to 57.1% in the training institutions. Those skills are important in order to increase the capability and employability of skilled construction workers. Besides, the involvement of contractors and construction related bodies in the training scheme should be increased in various aspect and they should also be responsible to play important roles in producing skilled workers since they are the most beneficial parties that widely using skilled workforce. Thus, the study is an important step towards the problem of skill workers in the Malaysian construction industry. The implementation strategies in integrating the role of training institutions and the construction industry would ensure that graduates from these training institutions are competent to fill the skill gap requirement by the various construction organisations